The drivers of universal health care in South Africa: The role of ideas, institutions and actors - Rebecca Surender (United Nations Research Institute for Social Development (UNRISD), 2014)
To address problems of inadequate public health services, escalating private healthcare costs and widening health inequalities, the South African government has launched a radical new proposal to introduce a universal health system for all South Africans; National Health Insurance (NHI). While most attention has been thus far devoted to the economics and fiscal affordability of universal coverage, relatively less attention has been paid to wider challenges - in particular the important role played by key stakeholders tasked with designing and implementing the reforms. This paper outlines the opportunities and challenges posed by the proposed NHI reforms in South Africa. It begins by explaining the countrys current system of health care provision including its human resource structure, functions and cost implications. It then summarizes the deficits and limitations of the current two-tiered health system and discusses what NHI is trying to achieve within this context and how it hopes to address the problems. Finally, the paper examines the political and institutional challenges the reforms will face with a particular focus on the actors involved. The findings suggest that the government will face considerable challenges to its proposed reform path and that the eventual design of the new system may have to be a compromised version of the system envisaged in the original Green Paper. In particular the government will face significant challenges in garnering the support of sections of the medical profession tasked with implementing the reforms.
Keywords: 330